MARXISME DAN ISLAM BAGAIMANA MANUSIA DIPERIKAN? - Firdaus Achmad (The Pontianak State Institute of Islamic Studies, 2013)
Right wing and left wing are the terms used by many people in judging the emergence of two giant paradigms: Islam and Marxism. Right wing describes the appearance of Islam, while left wing is attributed to the concept and application of Marxism. Substantially, “right” has the nation of good, positive characters, obedience, and decency. On the contrary, “left” portrays the symbols of bad, negative characters, disobedience, threat, and immorality. Although the interpreta-tion of the meaning of right and left is solely based on the root of human language culture, people have historically accepted right and left as good and bad. However, as this paper point out, Islam has yet to represent the paradigm and the right wing movement nor does Marxism represent the left wing since there good thing and truth in Marx‟s ideas.